2013
DOI: 10.1519/jsc.0b013e31827367cd
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome Risk Factors in High School and NCAA Division I Football Players

Abstract: Metabolic syndrome (MetSyn) is a clustering of metabolic and cardiovascular disease risk factors. The purpose of this study was to determine the prevalence of MetSyn risk factors in high school (HS) and college (College) football players and to examine if the prevalence varied according to body fat percent (%Fat). One hundred twenty-three males (height 179.0 ± 6.7 cm; weight 89.4 ± 19.6 kg) from 7 different high schools and 82 males (height 186.2 ± 6.8 cm; weight 99.6 ± 16.8 kg) from one university participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 25 publications
(54 reference statements)
2
33
0
4
Order By: Relevance
“…These data are corroborated by recent reports, which present evidence of risk factors of metabolic syndrome in NCAA athletes (4,19). Apparently, regular exercise may not be enough to balance other factors, such as genetics and/or poor diet, which may promote excessive body fat and, subsequently, alter glucose metabolism.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These data are corroborated by recent reports, which present evidence of risk factors of metabolic syndrome in NCAA athletes (4,19). Apparently, regular exercise may not be enough to balance other factors, such as genetics and/or poor diet, which may promote excessive body fat and, subsequently, alter glucose metabolism.…”
Section: Discussionsupporting
confidence: 81%
“…Consequently, avoiding the insults of prolonged hyperglycemia on muscle health is critical for athletes looking to maintain peak performance. Though the link between prolonged hyperglycemia and competitive athletes is weak, new evidence in high school and collegiate athletes indicates a growing prevalence of risk factors associated with metabolic syndrome including abdominal obesity and fasting hyperglycemia (4)(5)(6)19). These data, while not demonstrating the existence of prolonged hyperglycemia, do raise the likelihood that collegiate athletes may experience periods of acute hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously identified a proportional shift of accumulation of VAT, even in an athletic population, with increasing adiposity and total mass (9). Monitoring VAT both during and after a playing career, in addition to other body composition measures, will be important for athletes to maintain health and healthy metabolic function (5, 13,15, 25, 27). This study, which shows the mean VAT values for OL and DL to be 2 – 4 times greater than for the other positions, is consistent with our NFL population (9) and others that have shown linemen are at the greatest risk of cardiovascular and metabolic dysfunction after retirement (1, 2,18, 25, 31).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent advancements in DXA software allow for regional segmentation of body composition, comparison of right and left sides of the body, as well as the estimation of visceral fat mass (VAT). This additional information allows for a more detailed evaluation of the distribution of mass and the estimate of VAT has important implications for health and well-being of players (1, 5, 9, 1415, 25, 27). Researchers and sports performance trainers can use this information to determine mass distribution ratios that may have a stronger relationship with speed, strength and power than traditional total measures of body composition (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…24 However, even more concerning is that now even high school athletes are beginning to show signs of metabolic syndrome. Steffes et al 25 demonstrated that the rate of metabolic syndrome in high school football players is the same as that seen in college football players. They were even able to demonstrate that a high BMI and body fat percent were risk factors for developing metabolic syndrome.…”
Section: Health Risk Of Obesity In Athletesmentioning
confidence: 92%